COAGULATION SCREENS REQUESTED IN AN EMERGENCY DEPARTMENT: CLINICALLY INDICATED OR NOT?. Issue 9 (9th February 2016) - Park, K; Ahmed, N; Probst, F; Mitra, A; Ajayi, A; Zafar, K
Abstract : Objectives & Background: Emergency Department (ED) staff order blood tests for diagnostic work-up and to facilitate prompt treatment. However, with the emerging use of Rapid Assessment and Treatment (RAT) models aiming to provide early assessment by doctors, inappropriate investigations can be requested as a consequence. Our objectives were to establish whether coagulation screens performed in our London ED were clinically appropriate, and to determine its subsequent financial implications. Methods: Retrospective analysis of blood investigations performed was done using the ED computer system (Ascribe Symphony, UK). The first cohort was a random selection of approximately one-third of ED attendances during a one-week period in July 2013. Inclusion criteria were only patients who were seen by ED clinicians; patients seen directly by other specialties were excluded. Clinical notes were reviewed for every patient who had coagulation screens requested. A recently revised ED 'investigation matrix' was used as a local departmental standard. Up-to-date costs were obtained from the Pathology Department for common investigations (including a coagulation screen and D-Dimer for 2013/14). On the basis of initial results, implementations were introduced in the form of: staff teaching sessions, displaying of up-to-date cost figures, daily team read file and local posters highlighting the importance of cost prevention. The re-audit (second cohort) was performed 9 months later in May 2014 for all consecutive patients investigated by ED clinicians in a one-week period. Patients were included and excluded on the basis of the same criteria, with the same 'blood matrix' as a standard. Results: 70% of patients in the first cohort had blood tests (n=137). 54% of these patients had coagulation screens (n=74), 66% of them not being clinically indicated (n=49). From our initial findings, we projected an estimated loss of>£90, 000 per year. 52% patients in the second cohort had blood tests (n=370). 23% of these patients had coagulation screens (n=84), with 68% clinically inappropriate (n=57) based on our clinical criteria. Conclusion: Coagulation screens are sent in the majority of patients in the absence of clinical indications. A huge financial implication is associated with the investigations. A different approach is required in the ED to avoid inappropriate use of coagulation screens.